Early exercise testing and coronary angiography after uncomplicated myocardial infarction. Issue 6325 (1st May 1982) - Akhras, F; Upward, J; Stott, R; Jackson, G
Abstract : In a prospective study 61 patients aged 55 years or less with uncomplicated myocardial infarction underwent treadmill stress testing at two weeks and coronary angiography at six weeks after infarction. Of the 44 patients who had a positive stress test, 43 had additional severe coronary artery disease confirmed by coronary angiography. Of the 17 patients who had a negative stress test for additional disease, coronary angiography identified only single-vessel disease in the infarct area in 15. The sensitivity of the stress test was 95% and the specificity 94%, though the number of patients in the study was small. Thus, exercise testing has considerable potential for the early identification of multiple-vessel disease in patients with uncomplicated myocardial infarction.